9.EVALUATION OF PHOSPHO-AKT IMMUNOHISTOCHEMICAL EXPRESSION IN PATIENTS WITH LARYNGEAL SQUAMOUS CELL CARCINOMA (Iraqi Journal of Medical Sciences, 2018)
Background: Akt, is a serine/threonine protein kinase which act as an important regulator of cell proliferation and survival. The Akt complex is upregulated by phosphorylation producing phospho-Akt, which trigger a continued cell proliferation and survival and inhibit apoptosis, thereby promote cell survival.Objective: To evaluate the immunohistochemical expression of phosphorylated Akt (Phospho-Akt) in laryngeal squamous cell carcinoma (SCC) and to be correlated with different clinicopathological parameters.Methods: Phospho-Akt expression was investigated Immunohistochemically in 49 formalin-fixed paraffin embedded laryngeal SCC tissue sections collected from Teaching laboratories - Baghdad Medical City.Results: Phospho-Akt positive immunostaining appears in 57% of samples. Akt activation present in advanced stages of tumors with p value 0.02.Conclusion: The current findings may provide evidence that aberrant expression of Akt contributes to the pathogenesis (mechanism of disease development) of laryngeal SCC.Keywords: Akt, phospho-Akt, immunohistochemistry, laryngeal SCC, larynxCitation: Wanas NS, Mehdi LY, Alzubaidi LKA. Evaluation of phospho-AKt immunohistochemical expression in patients with laryngeal squamous cell carcinoma. Iraqi JMS. 2018; 16(2): 177-181. doi: 10.22578/IJMS.16.2.9
Keywords: Akt; phosphoAkt; immunohistochemistry; laryngeal SCC; larynx